Current Application of Mineralocorticoid Antagonist (MRA) in Heart Failure and CKD: Does Non-Steroidal Drug Add Novel Insights - Irene Carlino; Filippo Pirrotta; Luigi Gennari; Alberto Palazzuoli (Biomedicines)
Heart failure (HF) treatment evolved in the last 5 years with the introduction of new agents capable of reducing HF hospitalization and HF-related mortality. However, some categories such as patients with renal dysfunction tend to be excluded from larger randomized clinical trials. Additionally, most patients with HF experienced unavoidable glomerular filtration rate (GFR) deterioration during the clinical course. This is related to both cardio–renal interaction pathways and common cardiovascular risk factors that affect HF and chronic kidney disease (CKD). However, mineralocorticoid antagonists (MRAs) remain a cornerstone of HF therapy regardless of left ventricular ejection fraction (LVEF) values; some concerns remain about their utilization in CKD. Nevertheless, three studies (FIDELIO, FIGARO, and FINEARTS) have recently showed beneficial effects in both patients with HF and CKD associated with diabetes. Notably, finerenone a new non-steroidal MRA represents a significant step forward in cardiovascular therapy; its application spans a wide spectrum of HF phenotypes and CKD stages, and ongoing investigations will further elucidate its role in combination regimens and in broader patient populations. Further study may investigate the role of the drug in patients with heart failure with reduced ejection fraction (HFrEF) and in the severe CKD stage of non-diabetic etiology. In the current review paper, we provide a chronological overview of major trials evaluating the renal outcomes of MRAs, culminating in the emergence of finerenone as a novel therapeutic option for high-risk CKD populations, particularly those with type 2 diabetes mellitus (T2DM).